Polyoxometalate-based high-spin cluster systems: a NMR relaxivity study up to 1.4 GHz/33 T. Issue 41 (6th August 2019) - Ibrahim, Masooma; Krämer, Steffen; Schork, Nicolas; Guthausen, Gisela
Abstract : Paramagnetic polyoxometalates are of special interest with regard to their application as alternative contrast agents in nonhuman magnetic resonance imaging which is increasingly used in materials science and process engineering. Abstract : Paramagnetic polyoxometalates [RE30 Co8 Ge12 W108 O408 (OH)42 (OH2 )30 ] 56− (Rare Earth (RE): Gd, Dy, Eu, and Y) are of special interest with regard to their application as alternative contrast agents in non-human magnetic resonance imaging which is increasingly used in materials science and process engineering. This class of new paramagnetic materials promises detailed findings in the magnetic resonance images due to their rather large total electron spin on the one hand, i.e. large, field-dependent relaxivities up to the highest magnetic fields, and due to their relatively large cluster sizes with an impact on adsorption and penetration on the other hand. Apart from the magnetic field dependence, the sensitivity of relaxivities to motional correlation times will be shown for these polyoxometalates which is a prerequisite for modelling and understanding the physical behaviour of this new class of polyoxometalates in MRI. Also for the qualitative and quantitative interpretation of MR images, the knowledge of transverse and longitudinal relaxivities of the paramagnetic clusters in a given environment is mandatory. Examples considered in this publication are proteins in milk fractionation, the deposit of which was measured by MRI.